Notas nomenclaturales en Ophioglossum (Ophioglossaceae) - Meza Torres, Esteban Ismael (2015)
Nomenclatural notes in Ophioglossum (Ophioglossaceae). The lectotypes of Ophioglossum ellipticum Hook. & Grev. and O. macrorrhizum Kunze are selected. The plates of protologues and herbaria specimens were compared to choose them. Discussion and illustrations of the lectotypifications are given.